Development of a metric system measuring infrastructure sustainability: Empirical studies of Hong Kong. (1st January 2021) - Liu, Bingsheng; Xue, Bin; Chen, Xingbin
Abstract: Sustainable infrastructure development is an indispensable driving force for successfully advancing urbanization globally. Evaluation of Infrastructure Sustainability (IS) has become an area of research increasingly gaining scrutiny. However, there exists a knowledge gap of a formal and comprehensive metric system measuring IS in current studies. By reviewing infrastructure assessment studies and international rating systems, this study identified 64 metrics measuring IS. Building upon this, an empirical survey was designed and conducted to propose an IS metric system by analyzing 68 responding samples adopting ranking analysis and confirmatory factor analysis. This IS metric system consists of 4 measurement dimensions integrating the triple bottom line – environmental IS, social IS, and economic IS – with a fourth sustainability pillar of managerial IS. Three case studies evaluating sustainable infrastructures in Hong Kong were conducted to validate the formality and comprehensiveness of the developed IS metric system. It is claimed that, on the one hand, the IS metric system is formal enough to accommodate 4 dimensions, 15 criteria, and 50 metrics required for lifecycle IS evaluation. On the other hand, it is comprehensive enough to distinguish heterogeneous IS criteria adopted by multidisciplinary professionals in IS evaluation. The IS metric system not only contributes to the knowledge and practice in the field of multidisciplinary sustainability evaluation but also serves as a guide for infrastructure stakeholders making multidisciplinary decisions in terms of sustainable infrastructure developments. Highlights: A metric system measuring IS was developed based on empirical survey. Environmental, social, economic, and managerial sustainability were evaluated. Formality and comprehensiveness of the system were validated using case studies. Heterogeneous metrics are distinguishable across multidisciplinary professionals.